Essentials of finance : - Gallinger, George W. (Prentice-Hall, 1995)
Understanding that, for the majority of students, taking corporate finance may be their only exposure to the discipline, Essentials of Finance offers a broader perspective of finance, including corporate, investments, and financial markets and institutions. The first of its kind, this text recognizes that finance touches many aspects of business and everyday life, making it important for students in all business disciplines to have a broader understanding of finance. With an integrative approach, this unique text provides both majors and non-majors with a working knowledge of the terms, environment, and mechanics of finance and financial decision making, giving them an understanding of the importance of concepts related to creating shareholder value.